PENGARUH LATIHAN RELAY DRIBBLING DAN ZIG-ZAG DRIBBLING TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PESERTA EKSTRAKURIKULER SEPAK BOLA SMAN 1 LINGSAR - Rizqi Wahyu Akbar; Herman Syah; Nurdin (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study examined the effects of relay dribbling and zig-zag dribbling training on dribbling ability among participants in the football extracurricular program at SMAN 1 Lingsar. The study employed an experimental two-group pretest-posttest design involving 20 participants. Dribbling ability was measured using a field-diagram dribbling test administered before and after the intervention. Data were analyzed through normality and homogeneity testing followed by t-test analysis. The relay dribbling group improved from 60% at pretest to 75% at posttest, with an increase of 15% and a significance value of 0.05. The zig-zag dribbling group improved from 62% to 85%, with an increase of 23% and a significance value of 0.01. These findings indicate that both training methods improved dribbling ability, but zig-zag dribbling produced a greater improvement. Therefore, zig-zag dribbling can be considered the more effective method for improving dribbling ability in the context of school football extracurricular training.